Efficacy of bevacizumab with cisplatin and gemcitabine in Asian patients with advanced or recurrent non-squamous non-small cell lung cancer who have not received prior chemotherapy: A substudy of the Avastin in Lung trial - Mok T.S.K. (2014)
Aim: The phase III AVAiL study evaluated the efficacy and safety of the anti-vascular epidermal growth factor agent bevacizumab combined with platinum-based chemotherapy as first-line treatment in patients with advanced non-small-cell lung cancer (NSCLC). We report the results of a preplanned analysis of Asian patients enrolled in AVAiL. Methods: Patients with recurrent or advanced non-squamous NSCLC were randomized to receive bevacizumab 7.5mg/kg, bevacizumab 15mg/kg or placebo, plus cisplatin 80mg/m2 and gemcitabine 1250mg/m2 for up to six cycles, followed by bevacizumab or placebo until disease progression. An exploratory analysis was undertaken to assess efficacy and safety in an Asian subgroup. Results: Of the 1043 patients enrolled, 105 were Asian and were included in the subgroup analysis. Progression-free survival was 8.5months (95% CI 7.3-10.8) in the bevacizumab 15-mg/kg group, 8.2 (95% CI 6.6-11.7) in the 7.5-mg/kg group and 6.1 (95% CI 5.1-8.0) in the placebo group. Median overall survival in the 7.5-mg/kg bevacizumab group was prolonged compared with placebo group (HR 0.46; 95% CI 0.22-0.97). Nausea was the most common adverse event, occurring at similar rates (ranging from 69-76%) in all study groups. Hypertension was the most common adverse event of special interest, seen in 29, 55 and 16% of patients in the 7.5-mg/kg and 15-mg/kg bevacizumab and placebo groups, respectively. Conclusion: Study results strongly suggest that bevacizumab at a dose of 7.5mg/kg improves the duration of overall survival when combined with cisplatin-gemcitabine in Asian patients. Bevacizumab was well tolerated in this patient group. © 2011 Blackwell Publishing Asia Pty Ltd.